A Corpus-Driven Analysis of Student Translation Strategies for Culturally-Bound Quotations from English to Indonesian - Rakhmawati, Susi Septaviana; Supian, Supian; Dallyono, Ruswan; Hidayati, Farida; Lebedeva, Alexandra Leonidovna; Ladinata, Lsdinata (Makassar State University, 2025)
Abstract. Translation of quotes attributed to great personalities is a niche and rather less researched area of study within the discipline of translation studies. The quotations are often culture-bound and context-dependent and present some difficulties to translators due to the cultural and historical context of their creators. This paper has a two-fold purpose: (1) to explore the translation strategies employed by student translators in rendering culturally- and contextually-loaded quotations, and (2) to identify patterns in the application of these strategies based on the quotes’ textual features—such as sentence length, word order, and lexical particularities. In line with established translation research methodologies, this research adopts a corpus-driven analysis with interpretive elements. Strategies were identified and analyzed using a robust coding framework derived from established translation theories (e.g., Vinay, 1995; Molina, 2002; Abu-Ssaydeh, 2004) and specific corpus analysis tools like Wordsmith Tools. Comparison of 50 selected quotations—mostly chosen for their culture-bound content—exemplifies the use of an array of translation strategies, with paraphrasing and explicitation being the most frequently employed. Paraphrasing, as detailed in this paper, covers rewording involving syntactic and semantic adjustments. It occurred 18 times as a co-concomitant and 7 times singly. On some occasions, these strategies were used even when there were formal or idiomatic equivalents available in the target language. This indicates that student translators need more cultural sensitivity and strategic competence development, possibly through experiential hands-on training and longer training modules.Keywords: culture-bound quotations, corpus-based analysis, paraphrasing, student translators, translation strategies